Divergent trajectories of regeneration in early-successional forests after logging and wildfire - Bowd, Elle J; McBurney, Lachlan; Lindenmayer, David B (Ecological applications, 2025)
Increases in forest disturbances have altered global forest demography rates, with many regions now characterized by extensive areas of early-successional forest. Heterogeneity in the structure, diversity, and composition of early-successional forests influence their inherent ecological values from immediately following disturbance to later successional stages, including values for biodiversity and carbon storage. Here, using 14 years of longitudinal data, we describe patterns in the structure, richness, and composition of early-successional forests subject to one of three different disturbance types: (1) clearcut logging followed by slash burn, (2) severe wildfire followed by salvage logging, and (3) severe wildfire only, in the Mountain Ash (Eucalyptus regnans) and Alpine Ash (Eucalyptus delegatensis) forests of southeastern Australia. We also documented the influence of disturbance intervals (short, medium, and long) on early-successional forests. Our analyses revealed several key differences between forests that regenerated from wildfire versus two different anthropogenic perturbations. Most ash-type plant communities were resilient to wildfire within historical fire-regimes (75-150 years), exhibiting temporal trends of recovery in plant structure, richness, and composition within the first decade. In contrast, the richness, occurrence, and abundance of some plant lifeforms and life history traits were negatively associated with clearcut logging and salvage logging, relative to forests disturbed by wildfire alone. These included resprouting species, such as tree ferns and ground ferns. However, Acacia spp. and shrubs were more abundant after clearcut logging. Our findings also provide evidence of the pronounced negative impact of salvage logging on early-successional plant communities, relative to that of both clearcut logging and wildfire. Notably, plant richness declined for over a decade after salvage logging, rather than increased as occurred following other disturbance types. Early-successional forests provide the template for the stand structure and composition of mature forests. Therefore, altered patterns of recovery with different disturbance types will likely shape the structure and function of later-successional stages. Predicted increases in wildfire will increase the generation of early-successional forests and subsequent salvage logging. Therefore, it is pertinent that management consider how different disturbance types can produce alternate states of forest composition and structure early in succession, and the implications for mature stands.